Effect of non-stoichiometric solution chemistry on improving the performance of wide-bandgap perovskite solar cells. (March 2018) - Yang, Mengjin; Kim, Dong Hoe; Yu, Yue; Li, Zhen; Reid, Obadiah G.; Song, Zhaoning; Zhao, Dewei; Wang, Changlei; Li, Liwei; Meng, Yuan; Guo, Ted; Yan, Yanfa; et al.
Abstract: A high-efficiency wide-bandgap (WBG) perovskite solar cell is critical for developing perovskite-related (e.g., all-perovskite, perovskite/Si, or perovskite/Cu(In, Ga)Se2 ) tandem devices. Here, we demonstrate the use of non-stoichiometric precursor chemistry with excess methylammonium halides (MAX; X = I, Br, or Cl) for preparing high-quality ∼1.75-eV FA0.83 Cs0.17 Pb(I0.6 Br0.4 )3 perovskite solar cells. Among various methylammonium halides, using excess MABr in the non-stoichiometric precursor exhibits the strongest effect on improving perovskite crystallographic properties and device characteristics without affecting the perovskite composition. In contrast, using excess MAI significantly reduces the bandgap of perovskite due to the replacement of Br with I. Using 40% excess MABr, we demonstrate a single-junction WBG perovskite solar cell with stabilized efficiency of 16.4%. We further demonstrate a 20.3%-efficient 4-terminal tandem device by using a 14.7%-efficient semi-transparent WBG perovskite top cell and an 18.6%-efficient unfiltered (5.6%-efficient filtered) Si bottom cell. Highlights: Non-stoichiometric precursor chemistry for preparing high-quality wide-bandgap perovskite solar cells. Using excess MABr improves perovskite crystallographic properties and device characteristics. Using excess MAI reduces the bandgap of wide-bandgap perovskite due to the replacement of Br with I. Demonstrate a single-junction 1.75-eV perovskite solar cell with stabilized efficiency of 16.4%. Demonstrate a 20.3% 4-terminal tandem device with a 14.7% perovskite top cell and a 18.6% Si bottom cell.